Ecrire l’histoire du la - Fanny Gribenski (Revue d'anthropologie des connaissances)
Now commonly adopted as the point of reference for musicians in the Western world, A 440hz only became the standard pitch during an international conference held in London in 1939. Although musicians and musicologists are aware of the variability of musical pitches over time, as attested by the use of lower frequencies to perform early music repertoires, no study has fully explained the invention of our current concert pitch. This gap is surprising, especially when compared to the abundant literature dedicated to other processes of standardization– weight, measures, time– in the field of science studies. With this article, I suggest to fill this lacuna. In doing so, I show both what science studies bring to the history of musical practices, and, in turn, how sound as an object of study renews the our understanding of standardisation processes.